用因式分解法解下列方程(1-√3)y^2=(1+√3)y“√”代表根号还有一个(x-1)(x+3)-2(x+3)^2+3(x-3)(x+3)=0都是因式分解法
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 18:35:35
用因式分解法解下列方程(1-√3)y^2=(1+√3)y“√”代表根号还有一个(x-1)(x+3)-2(x+3)^2+3(x-3)(x+3)=0都是因式分解法用因式分解法解下列方程(1-√3)y^2=
用因式分解法解下列方程(1-√3)y^2=(1+√3)y“√”代表根号还有一个(x-1)(x+3)-2(x+3)^2+3(x-3)(x+3)=0都是因式分解法
用因式分解法解下列方程(1-√3)y^2=(1+√3)y
“√”代表根号
还有一个(x-1)(x+3)-2(x+3)^2+3(x-3)(x+3)=0
都是因式分解法
用因式分解法解下列方程(1-√3)y^2=(1+√3)y“√”代表根号还有一个(x-1)(x+3)-2(x+3)^2+3(x-3)(x+3)=0都是因式分解法
(1-√3)y^2=(1+√3)y
=(1+√3)y (y-1)=0,y=0或y=1
(x-1)(x+3)-2(x+3)^2+3(x-3)(x+3)=0
(x+3)(x-1-2x-6+3x-9)=0
(x+3)(2x-15)=0
x=-3或x=15/2
用因式分解法解下列方程;(2Y-5)⑵=3(5-2Y)
用因式分解法解下列方程 (y+2)(y-3)=6
用因式分解法,解下列方程,
用因式分解法解下列方程
用因式分解法解下列方程,
用因式分解法解下列方程,
用因式分解法解下列方程
用因式分解法解下列方程(x+3)²=9(1-2x)²
用因式分解法解下列方程:4(3x+1)^2-9=0
用因式分解法解下列方程:(2X-1)²=(3-X)²
用因式分解法解下列方程...急!用因式分解法解下列方程x²+3=3(x+1)
用因式分解法解下列方程4√2x-8=x^2
用因式分解法解下列方程;T(T-4√3)=-12
用因式分解法解下列方程 (x-3)^2+2x (x-3)=0
用因式分解法解下列方程x(x-2)=3(x-2)
用因式分解法解下列方程,(2x+3)∧2=24x
用因式分解法解下列方程x²+2ax-1-2a=0
用因式分解法解下列方程:(x十1)(x一3)=0